The role of team captains in integrating positive teammate psychological development in high-performance sport - Santos, F.; Strachan, L.; Gould, D.; Pereira, P.; Machado, C. (The Sport Psychologist, 2019)
Team captains play an important role in promoting positive life-skills development (PLSD) in their teammates. However, little research has been conducted to understand how team captains perceive the value of PLSD in high-performance sport. Therefore, the purpose of the present study was to understand how team captains integrate PLSD in high-performance sport. The participants in this study were 10 team captains from high-performance sports with teammates ranging from 14 to 38 years old. Data collection was conducted through 2 semistructured interviews. Results indicated that participants considered themselves PLSD-focused leaders and acknowledged the need to develop specific PLSD strategies. Nevertheless, team captains recognized the need to obtain support from their coaches to implement PLSD. Moving forward, coaches could provide a support system for athlete leaders to further enhance their ability to promote PLSD in high-performance sport.